An Optimal Strategy to Change the Non-Changeable Assets - Nezhadkian, Mahyar; Quan, Meicheng; Azimi, Seyed Mohammadtaghi (Management Analytics and Social Insights, 2024)
This paper introduces a novel strategy for modifying two ostensibly immutable assets in the market, employing the exchange option modeled and solved through a mesh-free numerical method based on radial basis functions. A specific currency market scenario is designed to assess its performance where two currencies remain unalterable. The strategy is then applied to this controlled environment, resulting in a redefined structure for exchange currency pricing. The numerical results, presented using MATLAB, illustrate the practicality and efficacy of our approach, contributing both a strategic framework for altering traditionally non-changeable assets and showcasing rigorous modeling and numerical methods in an academic context.